Comparing the Transfer Effects of Three Neurocognitive Training Protocols in Children With Attention-Deficit/Hyperactivity Disorder: A Single-Case Experimental Design. Issue 1 (3rd April 2023) - Zhang, Da-Wei; Johnstone, Stuart J.; Li, Hui; Luo, Xiangsheng; Sun, Li
Abstract: The current study used behavioural and electroencephalograph measures to compare the transferability of three home-based interventions — cognitive training (CT), neurofeedback training (NFT), and CT combined with NFT — for reducing symptoms in children with attention-deficit/hyperactivity disorder (AD/HD). Following a multiple-baseline single-case experimental design, twelve children were randomised to a training condition. Each child completed a baseline phase, followed by an intervention phase. The intervention phase consisted of 20 sessions of at-home training. Tau-U analysis and standardised visual analysis were adopted to detect effects. Results showed that CT improved inhibitory function and NFT improved alpha EEG activity and working memory. The combined condition, which was a reduced 'dose' of CT and NFT, did not show any improvements. The three conditions did not alleviate AD/HD symptoms. While CT and NFT may have transfer effects on executive functions, considering the lack of improvement in symptoms, this study does not support CT and NFT on their own as a treatment for children with AD/HD.